Effects of adiabatic and heat-conducting inserts in natural convection in inclined enclosures - da Silva G.M.F.* (2022)
© 2022 Taylor & Francis Group, LLC.Natural convection in a closed cavity with block-free, adiabatic and heat-conducting blocks was assessed for different inclination angles. The enclosure has vertical walls at different temperatures and adiabatic horizontal walls. The simulations were performed for the laminar regime and two-dimensional approximation. A cell-centered finite volume scheme was used to discretize the governing equations. This work addresses the influence of the Rayleigh number and cavity inclination in the flow pattern, temperature distribution, and local/global Nusselt numbers. It was observed that the largest heat transfer rates take place for heat-conducting blocks and inclination angles (Formula presented.) owing to higher velocity gradients.